2020
DOI: 10.2147/ndt.s274778
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electroacupuncture Relieves LPS-Induced Depression-Like Behaviour in Rats Through IDO-Mediated Tryptophan-Degrading Pathway</p>

Abstract: Background: Neuroinflammation is an important pathological mechanism of depression that leads to an increase in indoleamine-2,3-dioxygenase (IDO) activity and NMDAR activation. This study aimed to observe the effects of electroacupuncture on depressionlike behaviour in lipopolysaccharide (LPS)-treated rats and the underlying mechanism. Methods: Wistar rats were intraperitoneally administered LPS (0.5 mg/kg) for 7 consecutive days to establish a depression model. Electroacupuncture treatment was administered 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 61 publications
4
23
0
Order By: Relevance
“…Consistently, our results showed that, after 28 days of CUMS induction, the rats exhibited significantly reduced sucrose consumption, significantly lower numbers of crossings, and significantly increased immobility times in the FST, whereas EA reversed these changes and exerted effects similar to those obtained with FLX. This finding shows that EA exerts a good antidepressant effect, which is consistent with some of our previous research results [ 33 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Consistently, our results showed that, after 28 days of CUMS induction, the rats exhibited significantly reduced sucrose consumption, significantly lower numbers of crossings, and significantly increased immobility times in the FST, whereas EA reversed these changes and exerted effects similar to those obtained with FLX. This finding shows that EA exerts a good antidepressant effect, which is consistent with some of our previous research results [ 33 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…The rats were first fixed on a special fixator, and acupuncture needles (0.22 mm × 25 mm, Huan-Qiu, Suzhou Huanqiu Medical Appliance Co., Ltd., China) were inserted into the GV20 and GV29 acupoints ( Figure 2 ) at depths of 7 mm and 4 mm and connected to an electroacupuncture apparatus (Hwato SDZ-V, Suzhou Medical Supplies, China). The parameters of the electroacupuncture apparatus were determined according to our previous research [ 33 ]. Specifically, the waveform was an intermittent wave, the frequency was 2 Hz, and each EA treatment lasted for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study are consistent with previous studies, indicating that CUMS can induce depression-like behaviors and can effectively mimic the symptoms of patients with depression (Höflich, Michenthaler, Kasper, & Lanzenberger, 2019;Jiang et al, 2017;Watson, Harvey, McCabe, & Reynolds, 2020). Meanwhile, EA significantly ameliorated the CUMS-induced depression-like behaviors and exerted an obvious antidepressant effect, which is consistent with the previous studies Zhang, Liu, Gao, Ma, & Shen, 2020). Acupuncture, one of the conventional therapies in TCM, exerts therapeutic effects via modulating the nervous, endocrine, and immune systems (Zhou & Benharash, 2014).…”
Section: Discussionsupporting
confidence: 91%